Comparative Investigations onthe Main Elements of Carbon Fiber Based Composites Using Computational Structural Simulations. (March 2020) - Raj Kumar, G; Vijayanandh, R; Venkatesan, K; Ramesh, M; Senthil Kumar, M; Balaji, S
Abstract: A numerical investigation on main elements of composite material could provide the clear view on the selection of main elements for the construction of composites. The lifetime of composite material is basically depends upon the chemistry between reinforcement and matrix. Also, the improvements of properties in composite are based on the main elements. Therefore the comparative studies on main elements of composite could provide suitable components for composite, which have the high capability to provide high mechanical properties. In this work, a dog-bone shape test specimen is selected as fundamental component, which is modeled with the help of Design Modeller 16.2. Utterly, 25 test specimens are constructed depends on the fiber directional angle of the reinforcements for structural analysis. The numerical simulations on 40 specimens are executed completely and then comparative analyses are carried out. Finally, after the comparison, both reinforcement and matrix are optimized for tensile loading conditions.